Diagnostic efficiency of high-resolution ultrasonography in patients with chronic temporomandibular disorders - Thomas, Anju Elizabeth; Kurup, Seema; Kumar, Sreeja P.; Chandy, Marina Lazar; Jose, Renju (Oral radiology, 2016)
Purpose Temporomandibular disorders (TMDs) affect 8–12 % of the adolescent and adult population, resulting in patient discomfort and affecting quality of life. Despite the growing incidence of these disorders, an effective screening modality to detect TMDs is still lacking. Although magnetic resonance imaging is the gold standard for imaging of the temporomandibular joint (TMJ), it has a few drawbacks such as cost and its time-consuming nature. High-resolution ultrasonography is a non-invasive and cost-effective imaging modality that enables simultaneous visualization of the hard and soft tissue components of the TMJ. This study aimed to evaluate the correlations between the clinical signs and symptoms of patients with chronic TMJ disorders and their ultrasonographic findings, thereby enabling the use of ultrasonography as an imaging modality for screening of TMDs. Methods Twenty patients with chronic TMDs were selected according to the Research Diagnostic Criteria for TMDs. Ultrasonographic imaging of individual TMJs was performed to assess the destructive changes, effusion, and disc dislocation. Fisher’s exact test was used to examine the correlations between the findings obtained from the ultrasonographic investigation and the clinical signs and symptoms. Results There was a significant correlation between pain and joint effusion as well as between clicking and surface erosion. Conclusions The present findings suggest that ultrasonography can be used as a screening modality to assess the hard and soft tissue changes in patients presenting with signs and symptoms of TMDs.